Islamic Law and the State: An Analysis of the Relationship between Religious Authority and Political Power - Firayani Firayani (Journal of Nafaqah, 2025)
This article examines the relationship between Islamic law and the state through an analysis of authority contestation between religious institutions and political power. Employing a normative juridical method with conceptual and historical approaches, the study demonstrates that classical Islamic governance maintained a differentiated authority structure in which religious interpretation and political power operated within distinct normative spheres. The emergence of the modern state transformed this relationship by centralizing sovereignty and subordinating Islamic law to political control. Contemporary case studies reveal that excessive state intervention in religious matters undermines both legal legitimacy and religious authority. This article proposes a normative framework that emphasizes epistemic autonomy of religious authority, facilitative state governance, and clear institutional boundaries. The study contributes to contemporary debates by repositioning Islamic law as a normative system capable of coexistence with modern state structures without political instrumentalization.